2000
DOI: 10.1021/bi0006868
|View full text |Cite
|
Sign up to set email alerts
|

Differential Coupling through Val-344 and Tyr-442 of Trimethylamine Dehydrogenase in Electron Transfer Reactions with Ferricenium Ions and Electron Transferring Flavoprotein

Abstract: Modeling studies of the trimethylamine dehydrogenase-electron transferring flavoprotein (TMADH-ETF) electron transfer complex have suggested potential roles for Val-344 and Tyr-442, found on the surface of TMADH, in electronic coupling between the 4Fe-4S center of TMADH and the FAD of ETF. The importance of these residues in electron transfer, both to ETF and to the artificial electron acceptor, ferricenium (Fc(+)), has been studied by site-directed mutagenesis and stopped-flow spectroscopy. Reduction of the 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
54
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(63 citation statements)
references
References 33 publications
8
54
1
Order By: Relevance
“…Our difference spectroscopy studies reported in this paper provide direct evidence for impaired rates of complex assembly with the mutant TMADH enzymes (Table I), thereby supporting our previous kinetic model ( (18), see Discussion).…”
Section: Difference Spectroscopy and Kinetic Studies Of Complexsupporting
confidence: 89%
See 4 more Smart Citations
“…Our difference spectroscopy studies reported in this paper provide direct evidence for impaired rates of complex assembly with the mutant TMADH enzymes (Table I), thereby supporting our previous kinetic model ( (18), see Discussion).…”
Section: Difference Spectroscopy and Kinetic Studies Of Complexsupporting
confidence: 89%
“…3 in Ref. 18. Incubation of ETF sq and ETF ox with TMADH ox leads to a gradual ϳ4-fold increase in ETF flavin fluorescence, with a half-life of about 30 min and reaching a plateau after about 2 h (Fig.…”
Section: Fluorescence Properties Of the Electron Transfer Complex Andmentioning
confidence: 84%
See 3 more Smart Citations